Shaykh Ibrahim Niass : his revival of the Tijaniyya sufi order and response to colonialism - Abiodun, Abdul Ganiy Muhammad Raji
This research focuses on the revival efforts of Shaykh Ibrahim Niass and his response to colonialism in Western Sudan (West Africa) in the 20th century. The research also concentrates on the status of Islam and Muslims under the French colonial system in the last four decades of the nineteenth century through the 1960s of the 20thcentury. This is the period in which most of the West African countries came under European colonialism. This research documents how the Muslim scholars of the area under discussion resisted the colonial encroachment and penetration with all available mechanisms in their capacity. In order for the colonial authorities to have full control of the situation, they responded by exercising some policies against those Ulama'such as military force, by which they assassinated some of them such as Shaykh Umar al-Futi and exiled others like Shaykh Amadou Bamba, Shaykh Abdallah Niass and Shaykh Hamaullah. Similarly, the Ulama's free movement was restricted. The murid's actions of visiting their Shaykhs and offering them gifts were also forbidden. Above all, many madrasa were closed down and replaced by French secular schools. The study closely examines how Shaykh Ibrahim Niass responded to colonial hegemony and Christian evangelism. His response came when colonialism was at its peak in the late 1930s of the 20thcentury. His response was intellectual and educational rather than militant since the colonial authorities were advanced in military power more than the colonized. The research documents various peaceful approaches by which Shaykh Ibrahim Niass encountered the colonial policies in different aspects of life. His efforts to initiate a pan-African cum pan-Islamist front to encounter French colonialism are also investigated. Most notable among his efforts was his drive to expand and rejuvenate the Tijaniyya Order in West Africa and eventually in all parts of the globe.